2022
DOI: 10.1590/1980-549720220019
|View full text |Cite
|
Sign up to set email alerts
|

Environment modification at school to promote physical activity among adolescents: a cluster randomized controlled trial

Abstract: Objective: To assess the effect of modifications of the school environment on physical activity in Brazilian adolescent students. Methods: Seven public schools in Duque de Caxias (Brazil) were randomized into control and intervention groups. The intervention group underwent modifications in the school environment (painting of hopscotch and school courts) and the provision of sports equipment (balls, basketball table, soccer goalpost, volleyball nets, and others) to stimulate physical activity. Additionally, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Crust and colleagues [ 40 ] found no influence on children’s physical self-perception but observed positive effects on physical activity and pro-social behaviour with added markings. Benthroldo et al [ 41 ] in Brazil did not find a significant effect on self-reported physical activity after adding markings and loose equipment to public schools. Finally, a repetition study in France [ 42 ] reported a significant positive effect on accelerometer-measured physical activity using the same markings intervention as Ridgers and colleagues [ 35 , 36 ] in the UK.…”
Section: Resultsmentioning
confidence: 99%
“…Crust and colleagues [ 40 ] found no influence on children’s physical self-perception but observed positive effects on physical activity and pro-social behaviour with added markings. Benthroldo et al [ 41 ] in Brazil did not find a significant effect on self-reported physical activity after adding markings and loose equipment to public schools. Finally, a repetition study in France [ 42 ] reported a significant positive effect on accelerometer-measured physical activity using the same markings intervention as Ridgers and colleagues [ 35 , 36 ] in the UK.…”
Section: Resultsmentioning
confidence: 99%